DEVELOPMENT OF GARDEN LAND AS AN EFFORT FOR CULTIVATION OF FRUIT PLANTS IN POTS FOR PKK CADRES - Rita Syntia; Ary Kiswanto Kenedi; Asnawi; Bunga Mulyahati (LPPM dan PM Universitas Samudra, 2022)
This PKM is motivated by the inadequate empowerment of PKK cadres in Aceh Tamiang Regency in utilizing the coral environment in their respective villages and the lack of maximum knowledge of cadres in cultivating potential plants through the tabulakar and tabulampot systems. The purpose of this PKM is to train PKK cadres in Aceh Tamiang Regency to maximize the potential of the yard in rural areas by using the tabulampot system so as to increase community welfare with a creative economic system. The method of implementing this PKM activity is to use the method of applying science and technology which is carried out with a system of training and mentoring for tabulampot activities. The results of PKM that have been achieved are increasing the knowledge and skills of PKK cadres in Aceh Tamiang Regency in cultivating potential plants through the system and tabulampot.